Open membranes are the precursors for assembly of large DNA viruses. (5th July 2013) - Suárez, Cristina; Welsch, Sonja; Chlanda, Petr; Hagen, Wim; Hoppe, Simone; Kolovou, Androniki; Pagnier, Isabelle; Raoult, Didier; Krijnse Locker, Jacomine
Summary Nucleo cytoplasmic large DNA viruses (NCLDVs) are a group of double‐stranded DNA viruses that replicate their DNA partly or entirely in the cytoplasm in association with viral factories (VFs). They share about 50 genes suggesting that they are derived from a common ancestor. Using transmission electron microscopy (TEM) and electron tomography (ET) we showed that the NCLDV vaccinia virus (VACV) acquires its membrane from open membrane intermediates, derived from the ER. These open membranes contribute to the formation of a single open membrane of the immature virion, shaped into a sphere by the assembly of the viral scaffold protein on its convex side. We now compare VACV with the NCLDV Mimivirus by TEM and ET and show that the latter also acquires its membrane from open membrane intermediates that accumulate at the periphery of the cytoplasmic VF. In analogy to VACV this membrane is shaped by the assembly of a layer on the convexside of its membrane, likely representing the Mimivirus capsid protein. By quantitative ET we show for both viruses that the open membrane intermediates of assembly adopt an 'open‐eight' conformation with a characteristic diameter of 90 nm for Mimi‐ and 50 nm for VACV. We discuss these results with respect to the common ancestry of NCLDVs and propose a hypothesis on the possible origin of this unusual membrane biogenesis.